Avaliação do uso de armadilhas para captura de mosquitos associada a ferramentas de análise espacial como indicadores para vigilância entomológica e epidemiológica de dengue - Parra, Maisa Carla Pereira (2014)
Introduction: The dengue is the most important vector-borne worldwide. It’s caused by one of four serotypes of dengue virus (DENV1-4), which belong to Flavivirus genus. It is transmitted to humans by the bite of Aedes mosquitos, especially Aedes aegypti. This vector is adapted to human environments and water containers created by humans are their breeding sites. In this study, we performed a screening for the circulating serotypes of DENV in mosquitos from an area in São José do Rio Preto – SP (Brazil), associated with spatial analysis tools as entomological and epidemiological indexes for dengue. Materials and Methods: BG-Mosquitito and BG-Sentinel traps were installed at residences to capture mosquitos from the area. The mosquitos were pooled according to the gender and species and had the viral RNA extracted. The pools were tested by Multiplex-RT-PCR with Flavivirus generic primers followed by Nested assays with species-specific primers for DENV. Every sample was geocoded and weekly and fortnightly maps were created. Results: Nearly 3,000 trap collections were performed and 1,645 Aedes aegypti mosquitos (671 males and 974 females) were collected. The 893 pools presented 2.8% positivity for the DENV-4. We geocoded all collection addresses along the reported dengue cases in the neighborhood (confirmed as positive or negative by the laboratory exam). Conclusions: The use of traps to collect adult mosquitos was not sufficient for detecting the presence of infected mosquitos before the occurrence of human dengue cases. However, the use of geostatistical techniques associated with entomological indexes and dengue cases may provide the relative risk of dengue occurrence and together, they could be use in point of care interventions.